ACToday Columbia World Project leveraged CCAFS collaboration and research to develop capacity, support national-level policy development, and deploy curriculum, bringing enhanced climate services and knowledge to governments, other stakeholders, and communities in multiple countries. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The ACToday project has leveraged and deepened the collaboration between CCAFS and the International Research Society for Climate and Society (IRI) at Columbia University. Together, CCAFS and IRI have developed capacity, delivered tools, supported policy development, and deployed curriculum around climate services in multiple countries and at regional levels.